2017
DOI: 10.1038/srep39654
|View full text |Cite
|
Sign up to set email alerts
|

Promotion of natural tooth repair by small molecule GSK3 antagonists

Abstract: The restoration of dentine lost in deep caries lesions in teeth is a routine and common treatment that involves the use of inorganic cements based on calcium or silicon-based mineral aggregates. Such cements remain in the tooth and fail to degrade and thus normal mineral volume is never completely restored. Here we describe a novel, biological approach to dentine restoration that stimulates the natural formation of reparative dentine via the mobilisation of resident stem cells in the tooth pulp. Biodegradable,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
158
3
6

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 157 publications
(171 citation statements)
references
References 28 publications
4
158
3
6
Order By: Relevance
“…Severe tooth trauma caused by deep caries removal or tooth preparation may result in necrosis of the dental pulp tissue if the natural reparative dentine formation is insufficient to effect a proper repair (Neves et al . ). The present results have shown that the application of 0.4‐T static magnetic field promotes DPSC proliferation, migration and dentinogenic differentiation through the activation of the p38 MAPK signalling pathway.…”
Section: Resultsmentioning
confidence: 97%
See 1 more Smart Citation
“…Severe tooth trauma caused by deep caries removal or tooth preparation may result in necrosis of the dental pulp tissue if the natural reparative dentine formation is insufficient to effect a proper repair (Neves et al . ). The present results have shown that the application of 0.4‐T static magnetic field promotes DPSC proliferation, migration and dentinogenic differentiation through the activation of the p38 MAPK signalling pathway.…”
Section: Resultsmentioning
confidence: 97%
“…Neves et al . () applied three different glycogen synthase kinase 3 (GSK3) inhibitors to exposed animal dental pulp and found that all three antagonist groups exhibited a more obvious reparative dentine formation tendency than the sham control group or a mineral trioxide aggregate (MTA) group. Several studies have shown that the dentinogenic behaviour of DPSCs is affected by the mechanical properties of the extracellular microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Em um estudo coordenado por Neves et al (2017), foram testados inibidores da molécula de GSK-3, BIO (2'Z, 3'E)-6-bromoindirubina-3'-oxima),…”
Section: Figura 1 Efeitos De Gsk-3 Na Atividade Da Enzima Glicogêniounclassified
“…No procedimento experimental, realizado por Neves et al (2017), a perfuração foi realizada nos dois primeiros molares superiores dos animais e as esponjas foram inseridas e deixadas por 4-6 semanas antes da remoção. Para proteger a polpa da contaminação externa e estimular o reparo da dentina, a lesão foi oclusa com o agregado de trióxido de minério (MTA).…”
Section: Figura 1 Efeitos De Gsk-3 Na Atividade Da Enzima Glicogêniounclassified
See 1 more Smart Citation